2002
DOI: 10.1080/0268869021000007560
|View full text |Cite
|
Sign up to set email alerts
|

Are routine preoperative CT scans necessary in the management of single suture craniosynostosis?

Abstract: CT scanning is accepted as a regular component of the investigation of patients with simple craniosynostosis. In a series of 109 cases with simple craniosynostoses treated at Great Ormond Street Hospital for Children, a correct diagnosis on the basis of clinical findings was made in 100% of cases by an experienced clinician. CT scans with 3D reconstructions provided diagnostic confirmation in 100% of the patients when performed, but 91% of patients had already had sufficient confirmation of diagnosis by radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Our results showed that the use of an ultra-low-dose craniosynostosis CT protocol could reduce patient dose by more than 80% compared to our standard craniosynostosis scanning protocols, without compromising adequate image quality. We achieved sufficient image quality in our limited phantom study with CT protocols, resulting in an approximately 20 μSv effective dose for the patient, which is comparable to the effective dose of plain skull radiography (between 0.01 mSv and 0.04 mSv) [21,22]. However, the effective dose is used here for the purpose of comparison with other dosimetric studies and cannot be strictly considered as a measure of the stochastic radiation risk in children.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our results showed that the use of an ultra-low-dose craniosynostosis CT protocol could reduce patient dose by more than 80% compared to our standard craniosynostosis scanning protocols, without compromising adequate image quality. We achieved sufficient image quality in our limited phantom study with CT protocols, resulting in an approximately 20 μSv effective dose for the patient, which is comparable to the effective dose of plain skull radiography (between 0.01 mSv and 0.04 mSv) [21,22]. However, the effective dose is used here for the purpose of comparison with other dosimetric studies and cannot be strictly considered as a measure of the stochastic radiation risk in children.…”
Section: Discussionmentioning
confidence: 88%
“…However, the effective dose is used here for the purpose of comparison with other dosimetric studies and cannot be strictly considered as a measure of the stochastic radiation risk in children. Other studies for craniosynostosis CT have reported effective doses of 0.2-2.8 mSv [12,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 97%
“…Other researchers arrived at the conclusion that CT scanning in simple craniosynostoses did not provide any additional clinical benefit as a screening method for the detection of intracranial abnormalities or for surgical planning [74]. They propose that it may be appropriate to limit CT scanning-both axial images and 3D reconstructions-to selected cases where there is diagnostic uncertainty or where it is used in surgical planning [75].…”
Section: Authors' Preferred Diagnostic Approachmentioning
confidence: 98%
“…According to the evaluation of Gellad et al, cranial CT should be reserved for those cases in which the findings in the routine skull series are not clearly positive or negative, or in case of more complex craniofacial anomalies [74]. The concentration on the essential anatomic structures and lower milliampere-second settings results in a considerably reduced radiation dose and can be used for children without significant loss of information [35,[75][76][77].…”
Section: Authors' Preferred Diagnostic Approachmentioning
confidence: 99%
“…Since the advent of the As Low As Reasonably Achievable (ALARA) principle, a number of reports have investigated diagnostic radiology practice, including specific side effects of radiation doses 4 -14 and the role of radiologic studies in the evaluation of specific conditions such as craniosynostosis. [15][16][17][18] In plastic surgery, the concern over radiation dose in pediatric patients is a significant safety issue that has received only limited attention. The purpose of this report is to provide a summary of the clinical evidence relating risk and medical radiation, with specific emphasis on both the risks and utility of craniofacial imaging.…”
mentioning
confidence: 99%